52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0137
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Facility for Combustion Stability Experiments at Supercritical Pressure

Abstract: Combustion instability in liquid rocket engines can have severe consequences including degraded performance, accelerated component wear, and potentially catastrophic failure. High-frequency instabilities, which are generally the most harmful in liquid rocket engines, can be driven by interactions between disturbances associated with transverse acoustic resonances and the combustion process. The combustion response to acoustic perturbation is a critical component of the instabililty mechanism, and is in general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The GCSC injector was tested in the Combustion Stability Lab (EC-4) at Edwards AFRL CA, using RP-2 and gaseous oxygen. A detailed review of the complete system can be found in the work of Wegener et al 15 . The system has since been upgraded to accommodate liquid hydrocarbon propellants.…”
Section: Methodsmentioning
confidence: 99%
“…The GCSC injector was tested in the Combustion Stability Lab (EC-4) at Edwards AFRL CA, using RP-2 and gaseous oxygen. A detailed review of the complete system can be found in the work of Wegener et al 15 . The system has since been upgraded to accommodate liquid hydrocarbon propellants.…”
Section: Methodsmentioning
confidence: 99%
“…Ignition is achieved via a novel ignition system that will be described in future publications due to patent-related issues. Further background on the facility is described by Wegener et al 7 A variety of coaxial jet injector models have been investigated at AFRL under nonreacting flow conditions. 9,23 The coaxial jet injector geometry and near field flow dynamics are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work at AFRL has made major contributions towards understanding the coupling between acoustic waves and rocket injector flows in a nonreacting regime. [2][3][4][5][6][7][8][9] These experiments employed a high-pressure test facility that allowed for investigation of coaxial jets flowing inert surrogates, generally gaseous,liquid, and supercritical nitrogen, and exposing this shear flow to a variety of acoustic conditions that are representative of a transverse resonance that would occur in a rocket engine. In subcritical conditions, the center flow of the coaxial jet is cooled to a liquid condition, while the outer annular flow is chilled but maintained as a gas.…”
Section: Introductionmentioning
confidence: 99%
“…The facility is equipped with heat exchangers to allow cooling of the inner and outer injector flows. Further details on the experimental facility can be found in Wegener et al 7 A single coaxial jet injector was used for the experiments. The dimensions of the injector are summarized in Table 1.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%
“…2, 3 These flows have also been exposed to a range of transverse acoustic conditions. 4-6 A new experimental facility for reacting coaxial jet flows has been developed as described by Wegener et al 7 The present paper describes preliminary nonreacting data that was collected using this new facility. Although a large quantity of data has been collected in the past for nonreacting conditions, the current data considers a new framework in which to explore the forcing response of coaxial jets.…”
Section: Introductionmentioning
confidence: 99%